2019
DOI: 10.1101/737106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Haplotype genetic score analysis in 10,734 mother/infant pairs reveals complex maternal and fetal genetic effects underlying the associations between maternal phenotypes, birth outcomes and adult phenotypes

Abstract: Many maternal traits are associated with a neonate's gestational duration, birth weight and birth length. These birth outcomes are subsequently associated with late onset health conditions. Based on 10,734 mother/infant duos of European ancestry, we constructed haplotype genetic scores to dissect the maternal and fetal genetic effects underlying these observed associations.We showed that maternal height and fetal growth jointly affect the duration of gestationmaternal height positively influences the gestation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Taking advantage of the phasing of the children's genotypes, we could infer the parent-of-origin of the genotyped alleles as done by Chen et al 65 . This results in an alternative model that allows studying the association per haplotype in the set of unrelated trios, as detailed in equation 7.…”
Section: Child-mother-father Trio and Haplotype Analysismentioning
confidence: 99%
“…Taking advantage of the phasing of the children's genotypes, we could infer the parent-of-origin of the genotyped alleles as done by Chen et al 65 . This results in an alternative model that allows studying the association per haplotype in the set of unrelated trios, as detailed in equation 7.…”
Section: Child-mother-father Trio and Haplotype Analysismentioning
confidence: 99%
“…Several studies have shown associations of preterm birth and low birth weight with developmental disabilities such as cerebral palsy, intellectual disabilities, autism spectrum disorder, attention deficit hyperactivity disorder, learning disability and future risk of type 2 diabetes mellitus and cardiovascular diseases in child [40][41][42][43][44][45] . Understanding the genetic architecture of pregnancy phenotypes will not only elucidate the genetic basis of immediate health outcomes but also shed light on the nature of their relationships with long-term health outcomes 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of the phasing of the children genotypes, we could infer the parent-of-origin of the genotyped alleles as done by Chen et al 59 . This results in an alternative model that allows studying the association per haplotype in the set of unrelated trios, as detailed in equation 7.…”
Section: Methodsmentioning
confidence: 99%